Concussion knowledge among amateur motocross riders. (6th July 2016) - Miller, Kristina O; Langdon, Jody L; Burdette, Glenn P; Buckley, Thomas A
Aim: There has been considerable increase in concussion awareness and risks; however, extreme sports such as motocross have received scant attention. The purpose of this study was to assess concussion knowledge among motocross riders and determine differences based on demographic factors.Methodology & results: 782 motocross riders responded to an Internet-based questionnaire, and participant's knowledge score was 14.3 ± 2.7 out of 20 and symptom recognition was 6.8 ± 1.4 out of 8. Riders who had performed baseline concussion testing or received formal concussion education demonstrated higher knowledge scores. Rider's demographics did not predict outcome measures.Conclusions: Considerable misconceptions and lack of symptom knowledge persist among motocross riders and these results can be used for future interventions to improve concussion reporting.